Interpretasi Keluarga Ideal Perspektif Buya Hamka dan M. Quraish Shihab - Hafidzotun Nisa (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2022)
This article explains the concept of the ideal family contained in the interpretations of al-Azhar by Hamka and al-Misbah by Muhammad Quraish Shihab. These two interpretations show that the Qur'an contains instructions that can be used as a benchmark for humans to achieve the ideal family, namely humans must always present feelings of sakinah, mawaddah, and rahmah in their family. Apart from that, they also have to protect each other from things that can lead them to the fires of hell, wishing each other well. The views of the two interpretations are very relevant to modern life, that the values of the Koran must exist in the family to achieve an ideal family. The method used in this study is descriptive-qualitative using the interpretations of al-Azhar and al-Mishbah as data sources by limiting them to surah al-Rūm 21, QS. al-Taḥrīm 6 and QS. al-Furqān 74. The views of the two interpretations are compared, then enriched by the views of other commentators and figures.